2014
DOI: 10.1177/1078155214559113
|View full text |Cite
|
Sign up to set email alerts
|

A survey of manufacturing and handling practices for monoclonal antibodies by pharmacy, nursing and medical personnel

Abstract: Monoclonal antibodies are most commonly handled according to cytotoxic drug standards and often in the absence of formal guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The results that were found in this study reinforce and confirm previous studies. [22][23][24] Our study highlights the potential risks that are associated with post-production handling of mAbs. First, appropriate storage conditions with regard to temperature are pivotal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results that were found in this study reinforce and confirm previous studies. [22][23][24] Our study highlights the potential risks that are associated with post-production handling of mAbs. First, appropriate storage conditions with regard to temperature are pivotal.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that mAbs are treated according to cytotoxic drug standards and often without formal guidelines. [22] Secondly, Crul et al reported compounding practices of mAbs across Europe via an email survey. The results of the survey provided a clear impression of the variety of device use in practice across Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of the clinician's survey recognised that both occupational health and non‐occupational health issues were important factors to consider when determining how and where a MAB should be prepared. Methodological detail and results from the survey are reported elsewhere …”
Section: Process For Guideline Developmentmentioning
confidence: 99%
“…Furthermore, the attitudes and beliefs of the risk to occupational health and safety associated with use of MABs varied by profession and deviated from the views of national and international occupational health and safety authorities. 15…”
Section: Introductionmentioning
confidence: 99%